Correlation of inflammatory markers with type 2 Diabetes Mellitus in Pakistani patients - Nadeem, Amina; Naveed, Abdul Khaliq; Hussain, Muhammad Mazhar; Raza, Syed Irfan (Journal of Postgraduate Medical Institute, 2013)
Objective: To study the levels of inflammatory markers in Type 2 Diabetes Mellitus Pakistani patients anddetermine their correlation with the disease. Methodology: This cross sectional study was conducted at Military Hospital, Rawalpindi, and Centre forResearch in Experimental and Applied Medicine (CREAM), Army Medical College, Rawalpindi, Pakistanfrom June 2011-June 2012. We determined the levels of Erythrocyte Sedimentation Rate (ESR), Total LeukocyteCount (TLC), Interleukin 6 (IL-6) and Tumor Necrosis Factor- alpha (TNF-Î±) in 72 patients withType 2 Diabetes Mellitus (T2DM) and 40 healthy controls. The levels were correlated with age, durationof the disease, Body Mass Index (BMI), lipid profile and insulin resistance. Results: ESR, TLC, IL-6 and TNF-Î± were found to be significantly higher in T2DM patients. There wasalso statistically significant difference in BMI, fasting blood sugar, insulin resistance and dyslipidemia(except LDL) between diabetic and control group. All inflammatory markers except TNF-Î± were positivelycorrelated with insulin resistance. Only TNF-Î± was found to be correlated to duration of the disease.Both TLC and Serum insulin were positively correlated to BMI. Inflammatory markers were not correlatedto dyslipidemia. Conclusion: This is the first study reporting levels of cytokines in Pakistani diabetic patients and healthycontrols. There is augmented inflammation in T2DM in Pakistani patients which plays role in higher insulinresistance in these patients. TNF-Î± levels increases with longer duration of the disease. Levels ofinflammatory markers are not correlated to BMI, dyslipidemia or increasing age.